Fanatisme Jamaah Pengajian Agama terhadap Guru Zuhdi di Masjid Jami Banjarmasin - Novisari, Novisari; Hairina, Yulia; Faridah, Siti (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2020)
Fanaticism is an over-zealous attitude towards a particular perspective or attitude regarding community practice. For the recitation pilgrims, the Zuhdi teacher himself has a figure that is one of the things that is positive for everyone, because the respected figure is considered to be able to provide benefits that are considered positive and deserve fanaticism from many communities. How a person interacts is inseparable from the environment that shapes a person's personality. This type of research is a descriptive-qualitative field research, the method used by the author is a method for examining an object from a state of condition or a system of thought from the subject, the researcher collects a number of data obtained directly from the research location using information obtained from the object research through data collection instruments namely observation and interviews. Because Zuhdi teacher recitation worshipers at the Mosque of Jami are very many and from various backgrounds. Data collection techniques used are fanaticism scale, semi-structured interviews, and non-participant observation with subjects totaling 4 people with characteristics of recitation congregation aged 20-50 years. Based on the results that researcher have obtained in all four subjects have a dimension of fanaticism, the amount of interest and love for one type of activity, S and MI subjects have a strong interest, while the MA and Z subjects have a very strong interest because it attaches photos of Master Zuhdi at home and even saves photos and his deeds in special notes. So, fanaticism is a concept adopted by someone who has contributed to his life and makes his emotions become more mature or wise. Fanaticism in this study is one form of love and belonging to a society/group of figures who are believed to have made a major contribution in themselves and their lives.